Z železnico do modernejšega Maribora: arhitektura in urbanizem Maribora med letoma 1846 in 1918 - Štuhec, Mojca (University of Maribor Press, 2016)
By Rail to Modern Maribor: Architecture and Urbanism of Maribor Between 1846 and 1918. The period between the spring of nations in 1848 and the outbreak of World War I in 1914 fundamentally changed the traditional image of Europe in many respects, contributing to the rapid modernization of political systems, the economy, transport and also architectural activity. At that time, Maribor quickly transformed from a small, sleepy provincial town into a representative urban center of Lower Styria. Despite its exceptional importance, this architectural production in Maribor has not yet been sufficiently comprehensively analyzed and presented roundly in monograph form. This gap is filled by the book of art historian Mag. Mojce Stuhec. Assoc. prof. dr. After presenting the state of research, outlining the architectural activity of the Habsburg Monarchy in the long 19th century and presenting the historical circumstances and sources for the city’s construction history, the author focuses on the review of key architectural monuments from the time of Maribor historicism. The final part presents an important but often overlooked issue of the organization of construction activity, the relationship between architects and building masters, and touches on the issue of clients.